The Contribution of Prospective Memory Performance to the Neuropsychological Assessment of Mild Cognitive Impairment. Issue 1 (2nd January 2016) - Lee, Stephen; Ong, Ben; Pike, Kerryn E.; Mullaly, Elizabeth; Rand, Elizabeth; Storey, Elsdon; Ames, David; Saling, Michael; Clare, Linda; Kinsella, Glynda J.
Abstract : Objective : Prospective memory difficulties are a feature of the amnestic form of mild cognitive impairment (aMCI). Although comprehensive test batteries of prospective memory are suitable for clinical practice, they are lengthy, which has detracted from their widespread clinical use. Our aim was to investigate the utility of a brief screening measure of prospective memory, which can be incorporated into a clinical neuropsychological assessment. Methods : Seventy-seven healthy older adults (HOA) and 77 participants with aMCI were administered a neuropsychological test battery, including a prospective memory screening measure (Envelope Task), a retrospective memory measure (CVLT-II), and a multi-item subjective memory questionnaire (Prospective and Retrospective Memory Questionnaire; PRMQ) and a single-item subjective memory scale. Results : Compared with HOA participants, participants with aMCI performed poorly on the Envelope Task ( η 2 = .38), which provided good discrimination of the aMCI and HOA groups (AUC = .83). In the aMCI group, there was a small but significant relationship between the Envelope Task and the single-item subjective rating of memory, with the Envelope Task accounting for 5–6% of the variance in subjective memory after accounting for emotional status. This relationship of prospective memory and subjective memory was not significant for the multi-item questionnaire (PRMQ); and, retrospective memory was not a significant predictor of self-rated memory, single-item, or multi-item. Conclusion : A brief screening measure of prospective memory, the Envelope Task, provides useful support to traditional memory measures in detecting aMCI.